Menopausal symptom burden as a predictor of mid- to late-life cognitive function and mild behavioral impairment symptoms: A CAN-PROTECT study. - Jasper F E Crockford; Dylan X Guan; Gillian Einstein; Clive Ballard; Byron Creese; Anne Corbett; Ellie Pickering; Adam Bloomfield; Pamela Roach; Eric E Smith; Zahinoor Ismail (PLoS ONE)
Background Recent evidence suggests the experience of menopausal symptoms (i.e., perimenopausal symptoms) may be associated with cognitive and behavioural changes. We investigated these two relationships in a sample of postmenopausal females. Design Cross-sectional observational study. Setting Participant data was collected from the Canadian Platform for Research Online to Investigate Health, Quality of Life, Cognition, Behaviour, Function, and Caregiving in Aging (CAN-PROTECT) study. Participants 896 postmenopausal female participants. Methods Menopausal symptom burden was operationalized by summing the total number of recalled perimenopausal symptoms experienced. Cognitive function was measured using the Everyday Cognition (ECog-II) Scale, with higher scores reflecting greater severity. Mild Behavioral Impairment (MBI) was measured using the Mild Behavioral Impairment Checklist (MBI-C), with higher scores reflecting greater severity. A negative-binomial regression model examined the relationship between menopausal symptom burden and cognitive function, while a zero-inflated negative binomial regression model examined the relationship between menopausal symptom burden and MBI symptoms. Models adjusted for age, years of education, age of menopausal onset, type of menopause, and hormone therapy (HT). Age of menopausal onset and use of HT in the two associations were investigated with moderation analyses. Results Greater menopausal symptom burden was associated with higher ECog-II total scores (b [95% confidence interval (CI)] = 5.37 [2.85, 7.97]) and higher MBI-C total scores (b [95% CI] = 6.09 [2.50, 9.80]). Use of HT did not significantly associate with ECog-II total scores (b [95% CI] = -10.98 [-25.33, 6.35]), however, HT was significantly associated with lower MBI-C total scores (b [95% CI] = -26.90 [-43.35, -5.67]). Conclusions Menopausal symptom burden is associated with poorer cognitive function and more MBI symptoms in mid- to late life. HT may help mitigate symptoms of MBI. These findings suggest that the experience of menopause may indicate susceptibility to cognitive and behavioural changes, both markers of dementia.